Analisis Tingkat Kepatuhan Wajib Pajak dalam Pembayaran Pajak UMKM di Kabupaten Sikka - Maria Stefania Daya Goran (Universitas 45 Surabaya, 2024)
This research aims to determine the level of taxpayer compliance in paying MSME taxes in Sikka Regency. This research uses quantitative descriptive research methods. Data was obtained by conducting interviews and documentation. The data analysis technique used is quantitative descriptive data analysis technique. The results of this research show that the level of compliance of MSME taxpayers in 2021 - 2023 in 3 (three) consecutive years has experienced low results in terms of percentage. The percentage of compliance level of MSME taxpayers in 2021 - 2023 is at the mastery level of 0 – 54% with a low standard score. because the achievement is below 54%. The level of MSME taxpayer compliance in 2021 – 2023 still cannot meet the target. This is due to a lack of knowledge about tax regulations, the service system for taxpayers is not satisfactory, there is a lack of awareness among MSME taxpayers in carrying out their obligations in paying taxes, and there is a lack of socialization or education provided to MSME taxpayers.